Histomorphology of the subcommissural organ in the horse - KUMAR, PAWAN; TIMONEY, JOHN F (The Indian Journal of Animal Sciences, 2011)
The present study conducted on 6 young (10-12 months of age) horses of either sex revealed that subcommissral organ was present on ventral aspect of posterior commissure and extended froln pineal gland to recessus mesocoehcus fowlloing roof of III ventricle of the brain and partly of cerebral aqueduct. The organ was fully developed and comprised an ependyma towards the free ventricular surface, a hypendylna close to posterior commissure, and a sub-ependymal glial zone in between the 2. In addition, a sub-hypendymal fibrous. zone was also noticed except the areas where hypendymal cells penetrated the fasciculi of posterior commissure. The pseudostratlhed columar Ciliated ependynla had 2 types of nuclei mainly towards the mid portion of the ependynla. The sub-ependymal glial zone was constItuted by basal cytoplasmic processes of the ependymal cells, a few glia cells, nerve fibres and lood capll1anes whereas the hypendyma had hypendymal cells in addition to the constituents of the sub-ependymal ghal zone. Â